2010
DOI: 10.1007/s00436-010-2079-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Cryptosporidium spp. antigen by ELISA method in stool specimens obtained from patients with diarrhea

Abstract: Cryptosporidium spp. is an important parasitic protozoan causing diarrhea in developing and developed countries. The agent causes severe life-threatening diarrhea especially in immunocompromised hosts. Diagnosis of the Cryptosporidium oocyst in stool samples by conventional microscopy is labor-intensive and time-consuming. Thus, we aimed to evaluate the usefulness of a copro-antigen enzyme-linked immunosorbent assay (ELISA) test in detecting Cryptosporidium spp. from fecal specimens. For this aim, microscopy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 4 publications
4
17
0
3
Order By: Relevance
“…This study also points out that frog samples sourced from Cryptosporidium oocysts as compared to flotation which agrees with previous reports [15].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study also points out that frog samples sourced from Cryptosporidium oocysts as compared to flotation which agrees with previous reports [15].…”
Section: Discussionsupporting
confidence: 92%
“…This poses a challenge for the water management system in the study area as pipe borne water will contain this organism which is highly resistant to chlorination of water, making the water unsafe for human consumption even after treatment of the water [15].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by El-Hamshary et al (2008), El-Settawy and Fathy (2012). However, Elgun and Koltas (2011) reported that ELISA had the highest score followed by PCR and AF stain, while Kehl et al (1995) ranked AF stain higher than ELISA.…”
Section: Discussionmentioning
confidence: 98%
“…Conflicting reports concerning the sensitivity of fecal immunoassays over microscopy were recorded (Kehl et al 1995). Different sensitivities of immunoassays for detection of Cryptosporidium coproantigen were reported (Morgan et al 1998;Abdel-Baki et al 2004;El-Hamshary et al 2008;Elgun and Koltas 2011;El-Settawy and Fathy 2012), possible explanation was that commercially available coproantigen detection formats react to different sets of surface epitopes using mAbs which may react weakly or may not react with antigens of different Cryptosporidium species in clinical samples. Added to this, microscopy and fecal immunoassays had a detection limit that had been reported to be 50,000-500,000 oocysts/g of stool (Smith 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Araştırmalarda farklı yöntemler kullanılmış olsa da geri kalmış ülkelerde, 2 yaş altı çocuklarda [6][7][8], evcil hayvan besleyenlerde [9], gastroenteritlilerde [10,11], beslenme yetersizliklerinde [11), homoseksüellerde, immünyetersiz bireylerde, seyahat edenlerde, sıcak ve nemli ortam ve mevsimlerde enfeksiyonun daha sık görüldüğü bildirilmektedir [2]. Bu çalışmaların bazılarında Cryptosporidium ookistlerinin klorlanmış sularla veya herhangi bir işleme tabi tutulmayan sularla enfeksiyona neden olabileceği belirlenmiştir.…”
Section: Introductionunclassified